Modern method for crater volume evaluation - Kučera, Jindřich; Mátl, Jan; Pachman, Jiří (Univerzita Pardubice, 2022)
Detonating an explosive below a ground level produces a crater in the soil. In an ideal case the crater may have a symmetric conical shape. However, based on the soil type or presence of rocks or other inhomogeneities, the resulting crater may have an irregular shape. In such a case the volume calculation using a simple method by hand measurement with meter traditionally applied may not provide sufficiently precise results. The use of a drone for the 3D scanning makes the technique applicable for evaluation of any size of crater which makes the method suitable for explosive´s evaluation as well as for non-intrusive documentation of effects of accidental explosions. Our work presents a modern method for the crater volume evaluation by drone-based photogrammetry. The crater is firstly 3D scanned, photographs converted to 3D model and volume of the crater evaluated.
Moderní metoda stanovení objemu kráteru
Keywords: crater test; crater volume; photogrammetry; kráterová zkouška; objem kráteru; 3D skenování; fotogrametrie; 3D scanning